A weighted Sobolev regularity theory of the parabolic equations with measurable coefficients on conic domains in Rd - Kim, Kyeong Hun; Lee, Kijung; Seo, Jinsol (Journal of Differential Equations, 2021)
We establish existence, uniqueness, and arbitrary order Sobolev regularity results for the second order parabolic equations with measurable coefficients defined on the conic domains D of the type D(M):={x∈Rd:[Formula presented]∈M},M⊂Sd−1. We obtain the regularity results by using a system of mixed weights consisting of appropriate powers of the distance to the vertex and of the distance to the boundary. We also provide the sharp ranges of admissible powers of the distance to the vertex and to the boundary.
Keywords: Conic domains; Measurable coefficients; Mixed weight; Parabolic equation; Weighted Sobolev regularity